Comparación de métodos de diseño análogo y asistido (cad) para la elaboración de puentes fijos en el laboratorio dental - Yucta León, Renato Abraham (2025)
In the field of dental mechanics, precision and aesthetics are critical in the fabrication of dental prostheses, especially fixed bridges. This study compared two design approaches: the traditional analogue method and computer aided design ( for the fabrication of fixed bridges in the dental laboratory, in order to identify the strengths and limitations of each approach. A systematic review of previous studies, including theses, scientific articles and journal publi cations, was conducted to assess the impact of each method on quality, efficiency and patient satisfaction. The results analysed parameters such as dimensional accuracy, manufacturing time, ease of use and final product aesthetics, as well as patient satis faction. The findings suggest that the CAD method provides greater accuracy and efficiency in the fabrication of fixed bridges, as well as improved final aesthetics. In contrast, the analogue method, although more labour intensive, offers advantages in sit uations requiring customisation and manual expertise. These results are valuable for informed decision making in dental practice and the training of dental technicians, promoting innovation and improving the quality of the dental service, to the benefit of both professionals and patients.